Psychotic symptoms and its associated factors relating to psychoactive substance use among the youth population in Northwest Ethiopia - Kassew, Tilahun; Tilahun, Sewbesew Yitayih; Alemayehu, Biruk Fanta; Getnet, Berhanie; Demilew, Demeke; Tarekegn, Gebrekidan Ewnetu; Alemu, Kassahun; Yesuf, Yassin Mohammed; Oumer, Mohammed; Mehari, Eden Abetu; Melkam, Mamaru; Nenko, Goshu (Frontiers in Psychiatry, 2023)
Background Substance use is associated with high rates of psychiatric symptoms including psychotic symptoms. Despite the severity of the problem, there are intervention gaps in Ethiopia. To combat this, relevant evidence is required to raise the awareness of service providers. This study aimed to assess the prevalence of psychotic symptoms and its associated factors among the youth population who uses psychoactive substances in the Central Gondar Zone, Northwest Ethiopia. Methods A community-based cross-sectional study was conducted among the youth population in the Central Gondar zone, Northwest Ethiopia, from 01 January to 30 March 2021. A multistage sampling technique was used to recruit the study participants. All data were collected using questionnaires assessing socio-demographic; family-related variables; Depression, Anxiety, and Stress Scale; Multidimensional Scale Perceived Social Support (MSPSS), and Self-Reporting Questionnaire (SRQ-24). The data were analyzed using the STATA 14 statistical program. Results A total of 372 young people who used psychoactive substances (79.57%, 53.49%, 34.14%, and 16.13% were consuming alcohol, Khat, tobacco/cigarette products, and other substances such as shisha, inhalants, and drugs, respectively) were included in the study. The prevalence of psychotic symptoms was 24.2% with a 95% CI: 20.1, 28.8. Being married [AOR = 1.87 95% CI: 1.06, 3.48], recent loss of loved ones [AOR = 1.97 95% CI: 1.10, 3.18], low perceived social support [AOR = 1.61 95% CI: 1.11, 3.02], and severe psychological distress [AOR = 3.23 95% CI; 1.64, 6.54] were the factors associated with psychotic symptoms among young people with psychoactive substances use at a p-value of < 0.05. Conclusion Psychotic symptoms related to psychoactive substances among the youth population in Northwest Ethiopia were high. Thus, it is better to give a special attention to the youth population with low social support and existing psychological distress concurrent with psychoactive substance use.